40.9k views
3 votes
( n + -2 ) x ( n - -4 ) = 27

What are the two n's?

User Zifius
by
5.0k points

2 Answers

4 votes

Answer:

9 and 3

Explanation:

27/3=9

There are 2 different ways to solve this equation.

Side note: subtracting a negative (4- -3) turns the equation into addition (4+3) and adding a negative (4+ -3) turns the equation into subtraction (4-3)

So the original equation: (n + -2)x(n - -4)=27

Turns into this: (n-2)x(n+4)=27

Way 1: (11-2)x(-1+4)=27

9x3=27

Way 2: (5-2)x(5+4)=27

3x9=27

Hope this helped! :)

User Ernestina Juan
by
5.3k points
3 votes

Simplify n + -2 to n - 2

(n - 2)(n + 4) = 27

Expand

n^2 + 4n - 2n - 8 = 27

Simplify n^2 + 4n - 2n - 8 to n^2 + 2n - 8

n^2 + 2n - 8 = 27

Move all terms to one side

n^2 + 2n - 8 - 27 = 0

Simplify n^2 + 2n - 8 - 27 to n^2 + 2n - 35

n^2 + 2n - 35 = 0

Factor n^2 + 2n - 35

(n - 5)(n + 7) = 0

Solve for n

n = 5, -7

User Carlosvin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.